Creating values, not defending values - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2026)
Based on the ordonomic approach to business and corporate ethics, this paper rejects the defensive politicization of 'Western values' as a management overextension, since executives lack both the legitimacy and the qualifications for such a mandate. Instead, it advocates for a strategic shift toward the proactive exercise of order responsibility. It conceptualizes leadership as an architecture of value creation networks. Such leadership requires specific management competencies for designing incentives (governance) and communicating shared narratives (sensegiving). – – Basierend auf dem ordonomischen Ansatz zur Wirtschafts- und Unternehmensethik lehnt dieses Papier eine defensive Politisierung 'westlicher Werte' als eine Management-Überforderung ab, weil Führungskräfte dafür weder legitimiert noch qualifiziert sind. Stattdessen plädiert es für einen strategischen Wechsel hin zur proaktiven Wahrnehmung von Ordnungsverantwortung. Es begreift Führung als eine Architektur von Wertschöpfungsnetzwerken. Solche Führung erfordert spezifische Managementkompetenzen zur Gestaltung von Anreizen (Governance) sowie zur Kommunikation gemeinsamer Narrative (Sensegiving).
urn:nbn:de:gbv:3:2-123456789-1175070
Keywords: M14; D02; A13; 330; Ordonomics; Order responsibility; Value creation networks; Governance; Sensegiving; Ordonomik; Ordnungsverantwortung; Wertschöpfungsnetzwerke